Optimized Dunaliella salina-Salvinia molesta Probiotic Feed Enhances Hemocyte-Mediated Immunity of Litopenaeus vannamei under Taura Syndrome Virus Challenge - Ryan Adi Taufiqurrahman; Reza Adrio Farezi; Fitri Khairunisa; Sabitha Helmi; Ratih Novita Praja; Arend Stam (Journal of Aquaculture Science, 2026)
Taura Syndrome Virus (TSV) is one of the diseases that is capable of causing mass mortality ranging from 40% to 90% during the post-larval and juvenile stages of vannamei shrimp. The prevention of viral diseases in shrimp generally relies on antibiotics or vaccines, but it's still not effective. The use of probiotic feed containing extracts from Dunaliella salina and Salvinia molesta can enhance shrimp immunity. This research aims to determine the optimization of D. salina and S. molesta carotenoids as an effective alternative for preventing Taura Syndrome Virus (TSV) based on in vivo test results. The methods used for this research are carotenoids from D. salina, which were extracted at peak density (day 6) using solvent extraction, while β-carotene was extracted by maceration using n-hexane for 24 hours under dark conditions. The obtained extract was stabilized with NaHCO₃ and further processed for microencapsulation. Biomass was Shrimp were given various feed formulations: F1 (conventional feed + injected with PBS solution 0.1 ml), F2 (conventional feed), F3 (1:1), F4 (1:2), F5 (2:1), all groups were exposed to 0.1 ml TSV virus, except F1.  Therefore, F4 was selected as the best formulation, as it was most effective in improving growth performance and survival rate, as well as acting as an immunostimulant by increasing hyaline, granular, and semi-granular cells based on in vivo test results.